2015
DOI: 10.1080/2162402x.2014.1002726
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating CD8+T lymphocyte count is independent of tumor TLR9 status in treatment naïve triple negative breast cancer and renal cell carcinoma

Abstract: Toll-like receptor 9 (TLR9) is a cellular DNA-receptor of the innate immune system that is widely expressed in cancers. We demonstrated that low tumor TLR9 expression predicts poor disease-specific survival in triple negative breast cancer (TNBC) and renal cell carcinoma (RCC). We hypothesized that this is because TLR9 expression affects tumor immunophenotype. To begin to test this, we compared the number of tumor infiltrating CD8 C T lymphocytes with TLR9 expression in treatment na€ ıve breast cancer (n D 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
(83 reference statements)
5
25
0
Order By: Relevance
“…Thus, when levels of MHC class I and II expression are low, fewer T cells and IFNγ-producing antitumor T cells are present in the resistant tumors. Clinical studies of anti-PD-1 nonresponding tumors have shown reduced numbers of TILs in these tumors (7), findings similar to what we observed in the anti-PD-1 resistant tumor model (Fig. 6E).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, when levels of MHC class I and II expression are low, fewer T cells and IFNγ-producing antitumor T cells are present in the resistant tumors. Clinical studies of anti-PD-1 nonresponding tumors have shown reduced numbers of TILs in these tumors (7), findings similar to what we observed in the anti-PD-1 resistant tumor model (Fig. 6E).…”
Section: Discussionsupporting
confidence: 88%
“…Because clinical studies have suggested that PD-L1 expression on tumor tissues correlates with objective response to anti-PD-1 therapy (57), we next studied the expression of PD-L1 on the parental and resistant tumor cells. The cell lines from in vitro culture showed similar PD-L1 expression levels (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, TNCs with TLR9 overexpression were significantly correlated with development of a fibrous (P = 1.2×10 −6 ) and inflammatory microenvironment (P < 10 −7 ) with accumulation of CAFs and MICs overexpressing TLR9 and numerous CD4 lymphocytes, Treg lymphocytes and CD8 CD45RO memory cells (P = 0.016). Moreover, high contents of stromal inflammation, CAFs and MICs overexpressing TLR9 and numerous cytotoxic CD8 lymphocytes were also associated with a better prognosis [43]. Cancer-associated chronic inflammation initiated by epithelial cancer cells and stromal/immune cells overexpressing TLR9, is amplified and sustained by a chemokine inducer composed of activated NF-kB and STAT3 [44,45] which may promote cancer progression and therapeutic resistance [46].…”
Section: Discussionmentioning
confidence: 99%